2022
DOI: 10.3748/wjg.v28.i24.2775
|View full text |Cite
|
Sign up to set email alerts
|

Is long-term follow-up without surgical treatment a valid option for hepatic alveolar echinococcosis?

Abstract: We read the article titled, “Long-term follow-up of liver alveolar echinococcosis using echinococcosis multilocularis ultrasound classification,” by Schuhbaur J with great interest. However, we found some worthwhile issues that we believe should be discussed with the authors, and have provided our comments in this letter. It would be valuable if the authors could provide further information about the clinical stages, follow-up time, and clinical outcomes of the patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…HAE is a zoonotic disease with severe clinical manifestations and poor prognosis. Currently, radical surgery combined with albendazole medication remains the most ideal treatment option for HAE patients [25][26] . In recent years, numerous studies have gradually revealed the ability of LncRNAs to regulate the expression of target genes through various pathways, playing a significant role in promoting the occurrence, development, and metastasis of tumors.…”
Section: Discussionmentioning
confidence: 99%
“…HAE is a zoonotic disease with severe clinical manifestations and poor prognosis. Currently, radical surgery combined with albendazole medication remains the most ideal treatment option for HAE patients [25][26] . In recent years, numerous studies have gradually revealed the ability of LncRNAs to regulate the expression of target genes through various pathways, playing a significant role in promoting the occurrence, development, and metastasis of tumors.…”
Section: Discussionmentioning
confidence: 99%
“…Treatment options for echinococcosis include surgery, chemotherapy, and a "watch-andwait" approach (Wen et al 2019). However, the optimal preventive and curative methods for different types or classifications of echinococcosis remain limited and controversial (Stojković et al 2018;Maimaitinijiati et al 2022). Emphasis on prevention of infection and disease occurrence could contribute to the reduction of the global echinococcosis burden.…”
Section: Introductionmentioning
confidence: 99%
“…2018; Maimaitinijiati et al . 2022). Emphasis on prevention of infection and disease occurrence could contribute to the reduction of the global echinococcosis burden.…”
Section: Introductionmentioning
confidence: 99%